A Studing the Reality of Rural Development in Latakia Governorate -Albahloulia District as a Model- - جحجاح , محسن; سليمان , حيان; محمد, نغــــم (Latakia University Journal -Biological Sciences Series, 2021)
This research aims to studying the reality of rural development in Al-Bahlulia area in the countryside of Latakia, along with the most important natural and human obstacles which affect the course of rural development process. It considers the social and economic characteristics of the intended area's inhabitants and their level of awareness towards issues related to education, health and environment. Moreover, the research addresses awareness of inhabitants of the role of the rural woman in the process of development there, in addition to finding out impacts of the crisis on several aspects of their lives. The descriptive method was adopted to gather, organize and analyze data in order to obtain information ,then deductions and generalizations using a questionnaire containing questions about inhabitants' current situation and actions taken to achieve rural development. The questionnaire was distributed to a sample consisting of 168 randomly selected families, living in four different randomly selected villages in the area. The study revealed that the area's inhabitants live below the poverty line. Also, the implemented economic indicators pointed to a state of unfair distribution of incomes among the individuals of the studied sample, in addition to an increase in unemployment rates, a decline in the performance of all aspects of the governmental service sector along with poor investments of available resources in the area, especially for agricultural and touristic purposes. The study presents some suggests and recommendations that meet inhabitants' needs and tackle their problems. These suggestions and recommendations aim to enriching the proposed development programs and plans and overcoming development obstacles for the purpose of achieving comprehensive and integrated development in the intended area.